Physical, Microbial, and Chemical Qualities of Dangke Produced by Different Temperatures and Papain Concentrations - Andi Nurul Mukhlisah; Irma Isnafia Arief; Epi Taufik (Faculty of Animal Science, Bogor Agricultural University, 2017)
Dangke, a dairy product of cow or buffalo, is a traditional food of Enrekang, South Sulawesi Province. Addition of papain in dangke preparation is responsible for the formation of solid texture of dangke. This study was aimed to find optimum conditions (temperature and concentration of papain enzyme) and their effects on physical, chemical, microbiological, and hedonic qualities of dangke. This study consisted of two stages: preparation of papain and dangke production with heating temperatures (70, 80, and 90 °C) and papain treatments (0.2%, 0.3%, and 0.4%). The experiment was conducted in a completely randomized design with a 3 x 3 factorial arrangement with three replicates. The first factor was the processing temperature consisted of 3 levels i.e., 70, 80, and 90 °C. The second factor was the papain concentration consisted of 3 levels i.e., 0.2%, 0.3%, and 0.4%. The obtained data were evaluated using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test to observe the significances among treatments. Papain and amino acids were characterized using descriptive methods and organoleptic study was performed by non-parametric test (Kruskal-Wallis). The highest protein concentration was found in commercial papain (Merck, 360.63 mg/100 g), while the protein content of papain used in this study was of 323.21 mg/100g. However, these enzymes had similar molecular weight of 19.17 kDa. The optimum condition of dangke preparation was found at heating temperature of 80 °C and 0.3% of papain concentration, resulting in the most desirable characteristics of dangke in terms of chemical, physical, and microbiological properties as well as hedonic evaluation.